Degradação fotocatalítica do princípio ativo sulfametoxazol utilizando como catalisadores o compósito de acetato de celulose/TiO2 e zinco recoberto com ZnO - Roos, Andreine Aline (2013)
Environmental contamination is a serious problem in today's society and for years aroused the interest of researchers. The pollutants with pharmacological activity are worrying the scientific community by increasing detection of these aquatic environments at concentrations ranging from µ L-1 to ng L-1, which are resistant to conventional treatments used in sewage treatment plants. Thus, it becomes necessary to investigate more effective treatments to minimize environmental contamination. The Advanced Oxidation Processes have attracted interest as promising treatments for removal of organic pollutants, among which stands out the heterogeneous photocatalysis whose the main drawback is the difficulty of separating the catalyst from solution degraded. To try to solve the problem, this work proposes the use of cellulose acetate/TiO2 composite and zinc metal plate coated with ZnO as catalysts for photodegradation of sulfamethoxazole. The composite was prepared by phase inversion of a solution of cellulose acetate and titanium tert-butyl orthotitanate that resulted in a composite with around 4% (in mass %) if TiO2.This composite proved not to be efficient in the degradation of sulfametoxazol in the presence of hydrogen peroxide under both, sunlight or artificial radiation. For this reason the continuity of the work occurred only with zinc plate coated with ZnO obtained by hydrothermal method. The 22 factorial experimental design, with triplicate on central point showed that the model was valid, and that the process was favored with increasing amounts of H2O2 at acidic pH. The equilibrium time for the photodegradation of sulfametoxazol using a plate Zn/ZnO was 120 minutes with removal of 95%, under artificial radiation, obeying the rate law of peudo-first order. The COD and nitrate concentration indicated that there was a small mineralization of the pollutant, despite the high removal, showing that there was probably the formation of intermediate species. Furthermore, the Zn/ZnO showed a catalytic efficiency almost unchanged up to 10 repetitions of photodegradation. However, at the end of the process the zinc concentration in the sample was above the allowed degraded by environmental agencies, necessitating the use of a post-treatment for removal of zinc or use of sulfametoxazol solution with pH closer to neutrality to avoid dissolution of the metal catalyst.